Is there a functional disadvantage to using the external iliac vessels for vascular anastomosis in children and adolescents undergoing renal transplantation?. (27th March 2019) - Lorenzo, Armando J.; Taylor, Katherine; Farhat, Walid A.; Gnech, Michele; Rickard, Mandy; Koyle, Martin A.
Abstract: Purpose: RT remains the best available strategy for addressing stage 5 chronic kidney disease in children and adolescents. Technical aspects of the procedure can have a clear impact on complications and health of the allograft, including DGF. Immediate optimal perfusion is paramount, thus choosing a target vessel has to take into account the flow demands imposed by an adult‐size kidney in a proportionally smaller recipient. Herein, we explore the hypothesis that vascular anastomosis location can impact DGF adjusting for patient age and body size. Methods: Retrospective review of a single institution referral center transplant database, including information on 156 patients. We collected data on patient characteristics (age, height, BSA, gender, preoperative need for dialysis), donor source (deceased vs living), WIT/CIT, hemodynamics during the procedure, use of inotropes or diuretics, and location of the arterial and venous anastomoses. The primary outcome, DGF, was assessed by measuring the ttNC (in days), adjusting for age and BSA. Results: Location of the arterial anastomosis was clearly impacted by age and donor size (Figure 1A). On univariate analyses, longer ttNC was associated with deceased vs living donor (11.8 ± 11.5 and 4.3 ± 5.0; P  < 0.001), preoperative need for dialysis (9.7 ± 11.0 and 6.5 ± 6.0, P  = 0.02), location of arterial anastomosis (aorta [n = 21] 4.9 ± 6.1, common iliac [n = 93] 7.1 ± 7.3, external iliac 14.7 ± 14.5; P  < 0.001, Figure 1B) and venous anastomosis (vena cava [n = 21] 5.6 ± 6.3, common iliac [n = 89] 7.1 ± 7.6, external iliac [n = 44] 13.8 ± 14); P  < 0.001). On multivariable analysis, this association remained statistically significant when adjusting for recipient age, height, BSA, donor source, change in blood pressure with unclamping, and use of inotropes and preoperative dialysis. The detrimental effect on ttNC was more salient when comparing external iliac vs common iliac and aorta or vena cava. Conclusion: Our data suggest that anastomosis to a smaller caliber target vessel (ie, external iliac) in comparison with the common iliac or aorta/vena cava may be a risk factor for delayed return of graft function, independent of recipient size and donor source. This finding merit further evaluation, as it may help with intraoperative decision making during pediatric and adolescent RT.